Technoeconomic analysis and optimization of hybrid solar/wind/battery systems for a standalone house integrated with electric vehicle in Saudi Arabia. (15th December 2021) - Al-Buraiki, Abdulrahman S.; Al-Sharafi, Abdullah
Highlights: Hybrid PV/Wind/Battery system is considered. Monthly electrical loads for a residential house in Saudi Arabia are utilized. Solar and wind potentials at different locations in Saudi Arabia are evaluated. Electric vehicle integration to a residential home electrical load is investigated. Abstract: This paper aims to optimize and assess the performance of a standalone hybrid PV/wind/battery system to meet the electrical load requirements of a residential house under different weather conditions at different locations in the Kingdom of Saudi Arabia, namely: Dammam, Riyadh, Jeddah, Buraydah, Tabouk and Sharurah. Two cases are considered in this study. In the first case, the hybrid system is sized to meet only the electricity demand of a residential house whereas in the second case the hybrid system is sized to meet the electricity demand of a residential house integrated with electric vehicle (EV). Mathematical models and MATLAB computer code are developed and used to determine the optimum sizes of the hybrid system components while minimizing the costs and maintaining high reliability. Different scenarios of the daily travelled distance by the EV are considered ranging from 25 to 100 km/day with increment of 5 km/day. The results showed considerable variations in the optimum system configurations at the considered locations due to different renewable energy potentials. For the scenario of an average daily travelled distance of 50 km/day, smaller hybrid system components sizes were needed for the locations with higher solar and wind renewable energy potentials as in Buraydah and Dammam where levelized cost of electricity (LCOE) of the optimum configurations were 0.4381 and 0.4417 $/kWh, respectively. However, due to the lower solar and wind renewable energy potentials in Sharurah, large hybrid system sizes were needed with higher LCOE of 0.5646 $/kWh. Tabouk, Riyadh and Jeddah, showed moderate hybrid system sizes with LCOE of 0.4775, 0.4884 and 0.4934 $/kWh, respectively.